Pengembangan Sistem Administrasi Berbasis Web Pada Optik Inty Menggunakan Model Prototype - Ghani Subekti, Altaf; Diaz Setiadi, Alvin; Wisnu Pradipta, Ryandanu; Haryono, Wasis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The development of information technology has driven digitalization across various sectors, including business administration. Optik Inty, an optical service provider, still relies on manual administrative processes, leading to inefficiencies and data recording errors. This study aims to develop a web-based administrative system to improve the efficiency of managing product data, customer records, transactions, and financial reports in an integrated manner. The system was developed using the prototype method, allowing continuous iterations based on user feedback. The system was tested using the Black-Box approach to ensure its functionality meets the required specifications. Test results showed that all features performed well, including product management, transaction processing, and financial reporting. This system enables Optik Inty to reduce recording errors and improve service speed, thereby supporting adaptive and sustainable digital transformation.